Tinjauan Yuridis Tentang Peran Manusia dalam Pengelolaan Lingkungan Hidup di Indonesia - Ameliya Rasidi; Widyawati Boediningsih (CV. ULIL ALBAB CORP, 2024)
This research examines the role of humans in environmental management in Indonesia from a juridical perspective. Using a normative juridical method, this study analyzes relevant legislation, particularly the 1945 Constitution, Law No. 32 of 2009, and Law No. 11 of 2020. The results show that the role of humans in environmental management has been comprehensively regulated, including social supervision, providing suggestions and opinions, and submitting information and reports. Despite regulatory changes, the basic principles of community participation are maintained. Active human participation has positive impacts, including increased transparency, equal partnerships, and strengthened sense of responsibility. However, its implementation still faces obstacles such as cultural, educational, and economic factors. This study concludes that the human role is crucial in maintaining environmental balance and recommends enhancing education and strengthening community participation mechanisms.